Usage of the apparatus of ordinary differential equations in modelling of economic and environmental systems - Oliynyk, A.P.; Grygorchuk, G.V.; Nezamay, B.S.; Feshanych, L.I. (Математичне моделювання в економіці, 2019)
The ordinary differential equations techniques applying to investigate the economical and ecological systems has been considered in presented article. The interconnected economical complexes development for the countries with the different economical potential has been simulated. The population economical activity influence on the environment pollution and the state of region’s flora has been investigated. The economical efficiency of the new technical diagnostics implementation has been studied. The methods of presented models realization has been presented and investigated, the results of tested calculations have been presented and one’s analysis has been given. The directions of future investigations have been determined.